Black phosphorus nanosheet hydrogels elicit a thermogenic effect and enhance diabetic wound healing through controlled drug release - Yangyang Li; Yujie Pan; Lingchao Kong; Haifei Long; Jianxiang Teng; Hao Zhen; Qiuyue Ding; Runsang Pan; Xiaobin Tian (Materials & Design)
Diabetic wounds, a common complication of diabetes mellitus, pose significant challenges in the domain of clinical treatment. The high glucose milieu leads to damage to the surrounding blood vessels and nerves, influencing the proliferation of endothelial cells. It triggers excessive reactive oxygen species (ROS) and an imbalanced inflammatory environment, which continuously inflicts pathological harm to the tissue and ultimately impedes wound healing. Deferoxamine (DFO), a drug utilized for the treatment of iron overload, has garnered considerable attention from scholars over the past decade due to its role in promoting angiogenesis, alleviating ROS, and regulating the immune environment. In this research, we loaded modified black phosphorus nanosheets (BPNSs) with DFO and combined them with injectable Gelatin methacryloyl (GelMA) to construct a multifunctional hydrogel that integrates mild photothermal therapy (PTT) and drug therapy. When the near-infrared light irradiates the hydrogel, it induces a warm stimulus and simultaneously enhances drug release. Once the near-infrared light is switched off, the hydrogel can slowly release DFO to achieve the effect of long-term drug release. BP and DFO collaborate to alleviate ROS, regulate the inflammatory response, promote angiogenesis, reverse the hypoxic state, and ultimately fulfill the function of facilitating the healing of diabetic wounds.